The Effect of Return on Risk Assets (RORA), Loan To Deposit Ratio (LDR) and Capital Adequacy Ratio (CAR) on Stock Prices (Empirical Study on Banking Sector Companies on the Indonesia Stock Exchange in 2020-2023) - Purwati, Asih; Mareta, Sigit (Journal of Accounting and Finance Management, 2024)
This study aims to determine the effect of Capital Adequacy Ratio (CAR), Loan To Deposit Ratio (LDR), Return On Risk Asset (RORA), on Stock Prices (Empirical Study of Banking Sector Companies on the Indonesia Stock Exchange 2020-2023). The approach used in this study uses a quantitative research approach, namely data that can be measured on a numerical scale. The data source used in this study is secondary data, this study has a population of 47 banking companies and a sample of 42 banking companies This research was tested using panel data analysis which was processed using Eviews Version 13. The results of this study are Return On Risk Asset (RORA) & Loan To Deposit Ratio have no effect on the price of banking shares listed on the IDX in 2020-2023, while the Capital Adequacy Ratio (CAR) affects the price of banking shares on the IDX in 2020-2023. The results of this study are expected to benefit decision makers in the banking sector, including bank executives, regulators, and investors. They can use these results as a basis for making strategic decisions regarding risk management, capital allocation, and investment decisions.